The Effect of Environmental Performance, Environmental Cost and Environmental Disclosure on Financial Performance of Energy Sector Companies Listed on The Indonesia Stock Exchange 2021-2023 - Romaida Hutajulu; Dimita H Purba; Lamria Sagala; Dompak Pasaribu (Program Studi Akuntansi Universitas Simalungun, 2025)
This study aims to analyze the influence of Environmental Performance, Environmental Cost, and Environmental Disclosure on Financial Performance. This study was conducted on energy sector companies listed on the Indonesia Stock Exchange for the 2021-2023 period . This study was conducted to analyze factors influencing Financial Performance, including Environmental Performance, Environmental Cost, and Environmental Disclosure. The approach used was quantitative with multiple linear regression analysis using SPSS 25. The research sample consisted of 17 companies. The results showed that partially environmental performance did not affect financial performance, partially environmental cost did not affect financial performance, and partially environmental disclosure did affect financial performance. Simultaneously, Environmental Performance, Environmental Cost, and Environmental Disclosure affected Financial Performance